High burden and genetic diversity of β-lactamase-producing Escherichia coli and Klebsiella pneumoniae causing community-acquired urinary tract infections in Southeastern Gabon - Yann Mouanga-Ndzime; Cyrille Bisseye; Annicet-Clotaire Dikoumba; Désiré Otsaghe Ekore; Michelle Bignoumba; Marie-Louise Mawili Mounguengui; Neil-Michel Longo-Pendy; Sylvain Godreuil; Barthélémy Ngoubangoye; Bolni Marius Nagalo; Richard Onanga (PLoS ONE, 2026)
Background The increasing prevalence of β-lactamase-producing Escherichia coli and Klebsiella pneumoniae in community-acquired urinary tract infections (CA-UTIs) represents a growing public health challenge in low-resource settings. Data from Central Africa remain limited. This study investigated antimicrobial resistance profiles and phylogenetic diversity of these pathogens in southeastern Gabon. Methods Patients presenting with CA-UTIs were screened, and isolates of E. coli and K. pneumoniae were collected. Antimicrobial susceptibility testing was performed using the Kirby–Bauer disk diffusion method and interpreted according to EUCAST 2024 guidelines. Phenotypic screening identified extended-spectrum β-lactamase (ESBL), AmpC, and carbapenemase production. Polymerase chain reaction (PCR) was used to detect ESBL genes ( bla- CTX-M-gp1 , bla- CTX-M-gp2 , bla- CTX-M-gp9 , bla- TEM , bla- SHV ), plasmid-mediated AmpC genes ( bla- CMY-1 , bla- CMY-2 , bla- ACT-1 , bla- ACC , bla- FOX , bla- DHA ), and the carbapenemase gene bla-OXA-48 . Phylogenetic grouping of ESBL-producing E. coli was determined using PCR targeting chuA, yjaA, Tsp E4.C2, and arpA. Results Among 3,026 screened patients, 949 CA-UTIs were confirmed, including 589 cystitis and 360 pyelonephritis cases, yielding 200 isolates: E. coli (124) and K. pneumoniae (76). Of these, 68 (34.0%) were ESBL producers, 17 (9.0%) AmpC producers, and 2 (1.0%) carbapenemase producers. ESBL producing isolates were significantly associated with male sex (47.0%, p = 0.02) and children ≤5 years of age (48.2%, p = 0.007). ESBL- and AmpC-producing isolates exhibited high resistance rates (20–100%) to β-lactams, fluoroquinolones, and trimethoprim–sulfamethoxazole, while retaining susceptibility to carbapenems, ceftazidime–avibactam, and nitrofurantoin (up to 100%). Molecular analysis showed predominance of bla- CTX-M-gp1 in E. coli (40% alone; 31% in combination with bla- TEM ). In K. pneumoniae, bla- SHV + bla- TEM (49%) and bla- SHV + bla- CTX-M-gp1 + bla- TEM (42%) were the most frequent gene combinations; one isolate carried bla- OXA-48 . ESBL-producing E. coli predominantly belonged to phylogroup A (48.6%). Conclusion Multidrug-resistant ESBL-, AmpC-, and OXA-48-producing E. coli and K. pneumoniae are circulating in community settings in southeastern Gabon. These findings underscore the need for strengthened antimicrobial resistance surveillance and evidence-based community-level interventions.